BZcon1, a SANT/Myb-Type Gene Involved in the Conidiation of Cochliobolus carbonum. Issue 8 (1st August 2014) - Zhang, Jun-xiang; Wu, Yi-xin; Ho, Honhing; Zhang, Hao; He, Peng-fei; He, Yue-qiu
Abstract: The fungal pathogen Cochliobolus carbonum (anamorph, Bipolaris zeicola ) causes Northern Leaf Spot, leading to a ubiquitous and devastating foliar disease of corn in Yunnan Province, China. Asexual spores (conidia) play a major role in both epidemics and pathogenesis of Northern Leaf Spot, but the molecular mechanism of conidiation in C. carbonum has remained elusive. Here, using a map-based cloning strategy, we cloned a single dominant gene, designated as BZcon1 (for Bipolaris zeicola conidiation), which encodes a predicted unknown protein containing 402 amino acids, with two common conserved SANT/Myb domains in N-terminal. The BZcon1 knockout mutant completely lost the capability to produce conidiophores and conidia but displayed no effect on hyphal growth and sexual reproduction. The introduced BZcon1 gene fully complemented the BZcon1 null mutation, restoring the capability for sporulation. These data suggested that the BZcon1 gene is essential for the conidiation of C. carbonum .